2022
DOI: 10.3389/fpls.2022.974795
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and genotype by environment interaction of two major cassava processed products in multi-environments

Abstract: Conversion of cassava (Manihot esculenta) roots to processed products such as gari and fufu before consumption is a common practice worldwide by cassava end-user for detoxification, prolonged shelf life or profitability. Fresh root and processed product yield are supposed to be equivalent for each genotype, however, that is not the case. Developing genotypes with high product conversion rate is an important breeding goal in cassava as it drives the adoption rates of new varieties. The objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Public breeding programs have been assessing improved genotypes on-station for genetic variability, heritability and stability of the food product yield and quality traits of interest. 9,10 Assessment of clones for food product traits at the last breeding stage using multi-disciplinary methodologies 4,11,12 provided evidence of the need for a deliberate shift in breeding priorities to user-focused, inclusive and gender-responsive approach. [11][12][13] Recent breeding activities have incorporated the assessment and inclusion of the post-harvest processing and consumer acceptability aspects, 4,14 informing breeders' selection accuracy and definition of genetic gains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public breeding programs have been assessing improved genotypes on-station for genetic variability, heritability and stability of the food product yield and quality traits of interest. 9,10 Assessment of clones for food product traits at the last breeding stage using multi-disciplinary methodologies 4,11,12 provided evidence of the need for a deliberate shift in breeding priorities to user-focused, inclusive and gender-responsive approach. [11][12][13] Recent breeding activities have incorporated the assessment and inclusion of the post-harvest processing and consumer acceptability aspects, 4,14 informing breeders' selection accuracy and definition of genetic gains.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial to facilitate the selection of genotypes for specific, dual or multipurpose food uses. 9 It is also essential to overcome the paucity of information regarding the stability of acceptability traits of cassava-eba food across cultural and environmental settings among its diverse consumers. Earlier research 4,6,15,16,18 has established that processor and consumer preferences are mainly related to the texture and color of the food products, which informed our focus on laboratory parameters related to these.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different genotypes exhibit variations in both the quantity and quality of the final product. 19,20 As a result, it is unclear what proportion of the phenotypic variation in gari yield and quality is due to genetics, environment, or/and processing factors and their interactions. For genetic improvements, breeders are interested in the proportion of variation attributed to genotype effect.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on genotypic variation of genotypes on traits related to gari/eba quality were mainly descriptive, and assessment was done using a limited number of varieties. 9,10,[20][21][22][23][24][25][26][27][28] For example, Almazan 25 screened 35 genotypes in two replications to study the influence of genotypes on gari quality. Though the study revealed a significant genetic variation for gari quality, it did not elucidate the nature and extent of genetic variation, heritability, and correlations with fresh root quality-related traits.…”
Section: Introductionmentioning
confidence: 99%